Four new species of Torrenticola (Acari, Hydrachnidia, Torrenticolidae) from Northeastern China - Gu, Xinyao; Jia, Lan; Jin, Daochao; Guo, Jianjun (Zootaxa, 2020)
Four new species of Torrenticola i.e. Torrenticola triextensio sp. nov., T. songhuaensis sp. nov., T. changbaiensis sp. nov., T. acrisarostrum sp. nov. are described from Jilin Province, P. R. China, bringing the total number of Chinese Torrenticola species to 36. This is the second report of water mites from Northeastern China in the last two decades.